That's Not What I Meant: How Misunderstanding Is Related to Channel and Perspective-Taking. (March 2017) - Edwards, Renee; Bybee, Brock T.; Frost, Jonathon K.; Harvey, Adam J.; Navarro, Michael
Misunderstanding is an integral and unavoidable element of communication. This article links misunderstanding theoretically to message interpretation and conflict, then presents the results of a study that examined relationships among misunderstanding, channel of communication, and three forms of perspective-taking. Participants ( n = 98) responded to scaled items and described experiences of misunderstanding. Results showed that face-to-face misunderstandings are more serious than those that occur in computer-mediated communication. Dispositional perspective-taking, situational perspective-taking, and partner's situational perspective-taking were correlated with features such as frequency of misunderstanding, use of integrative strategies, open communication, humor, personal offense, and communication satisfaction. In about two thirds of the reported misunderstandings, the problem occurred because of the tone of the message, an interlocutor took personal offense, and open communication was used to resolve it. The findings are consistent with predictions concerning perspective-taking and extend understanding of misunderstanding. Recommendations include examining misunderstanding, especially in CMC, in greater depth.